Potentiation of NMDA Receptor Function by the Serine Protease Thrombin - Gingrich, Melissa B. (J Neurosci, 2000)
Although serine proteases and their receptors are best known for their role in blood coagulation and fibrinolysis, the CNS expresses many components of an extracellular protease signaling system including the protease-activated receptor-1 (PAR1), for which thrombin is the most effective activator. In this report we show that activation of PAR1 potentiates hippocampal NMDA receptor responses in CA1 pyramidal cells by 2.07 ± 0.27-fold (mean ± SEM). Potentiation of neuronal NMDA receptor responses by thrombin can be blocked by thrombin and a protein kinase inhibitor, and the effects of thrombin can be mimicked by a peptide agonist (SFLLRN) that activates PAR1. Potentiation of the NMDA receptor by thrombin in hippocampal neurons is significantly attenuated in mice lacking PAR1. Although high concentrations of thrombin can directly cleave both native and recombinant NR1 subunits, the thrombin-induced potentiation we observe is independent of NMDA receptor cleavage. Activation of recombinant PAR1 also potentiates recombinant NR1/NR2A (1.7 ± 0.06-fold) and NR1/NR2B (1.41 ± 0.11-fold) receptor function but not NR1/NR2C or NR1/NR2D receptor responses. PAR1-mediated potentiation of recombinant NR1/NR2A receptors occurred after activation with as little as 300 pm thrombin. These data raise the intriguing possibility that potentiation of neuronal NMDA receptor function after entry of thrombin or other serine proteases into brain parenchyma during intracerebral hemorrhage or extravasation of plasma proteins during blood–brain barrier breakdown may exacerbate glutamate-mediated cell death and possibly participate in post-traumatic seizure. Furthermore, the ability of neuronal protease signaling to control NMDA receptor function may also have roles in normal brain development.